Pengaruh Persepsi Kemudahan Penggunaan Aplikasi dan Kualitas Layanan Digital terhadap Keputusan Pembelian Shopee pada Generasi Z di Kota Depok - Inda Siti Nurjanah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The development of digital technology has changed people's shopping habits, shifting transactions from conventional systems toward e-commerce platforms, one of which is Shopee, widely used by Generation Z. This study aims to analyze the influence of perceived ease of use and digital service quality on Shopee purchase decisions among Generation Z in Depok City. A quantitative causal-associative approach was used, with data collected through questionnaires distributed to 100 respondents selected through purposive sampling and analyzed using multiple linear regression with SPSS 22. The results show that perceived ease of use has a positive and significant effect on purchase decisions (t = 6.650; sig. = 0.000), and digital service quality also has a positive and significant effect (t = 6.839; sig. = 0.000). Simultaneously, both variables significantly influence purchase decisions (F = 74.718; sig. = 0.000), explaining 60.6% of the variance (R² = 0.606). These findings indicate that ease of use and digital service quality are key factors driving Shopee purchase decisions among Generation Z in Depok City, so Shopee needs to keep improving both aspects to strengthen consumer purchase decisions.